2019
DOI: 10.3390/cancers11111644
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Impact of SRC Expression on the Prognosis of Patients with Head and Neck Squamous Cell Carcinoma

Abstract: Aberrant SRC expression and activation is frequently detected in multiple cancers, and hence, targeting SRC has emerged as a promising therapeutic strategy. Different SRC inhibitors have demonstrated potent anti-tumor activity in preclinical models, although they largely lack clinical efficacy as monotherapy in late-stage solid tumors, including head and neck squamous cell carcinomas (HNSCC). Adequate selection and stratification of patients who may respond to and benefit from anti-SRC therapies is therefore n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Moreover, TSPAN1 overexpression is associated to the development of an EMT program as consistently observed in mice tumors and HNSCC patient biopsies. Our findings support the notion that SRC activation may contribute to metastatic dissemination in HNSCC [25] and provide additional evidence extending the association of SRC activation with EMT to other HNSCC subtypes (i.e., laryngeal and pharyngeal carcinoma) beyond previous observations in nasopharyngeal carcinoma [56].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, TSPAN1 overexpression is associated to the development of an EMT program as consistently observed in mice tumors and HNSCC patient biopsies. Our findings support the notion that SRC activation may contribute to metastatic dissemination in HNSCC [25] and provide additional evidence extending the association of SRC activation with EMT to other HNSCC subtypes (i.e., laryngeal and pharyngeal carcinoma) beyond previous observations in nasopharyngeal carcinoma [56].…”
Section: Discussionsupporting
confidence: 88%
“…Staining was done at room temperature on an automatic staining workstation (Dako Autostainer Plus), using the Dako EnVision Flex + Visualization System (Dako Autostainer, Denmark) with the following antibodies: anti-TSPAN1 monoclonal antibody Clone HPA011909 (Sigma-Aldrich Química SL, Madrid, Spain) at 1:50 dilution, anti-E-Cadherin (BD Biosciences #610181, San Jose, CA, USA) at 1:4000 dilution and active SRC monoclonal antibody Clone 28 (Thermo Fisher Scientific #AHO0051) at 1:300 dilution. The SRC antibody, which detects the active protein, has been previously described [25]. Counterstaining with hematoxylin was the final step.…”
Section: Ihcmentioning
confidence: 99%
“…In this study, the data of the core target genes on median survival of OSCC patients suggested that PIK3R1, SRC, AKT1, MAPK3, and VEGFA are potential therapeutic targets of SBG; there was a correlation with the survival time of OSCC patients. PIK3R1, SRC, AKT1, MAPK3, and VEGFA are common therapeutic targets for OSCC closely related to the survival and prognosis of OSCC patients [31,53,65,66], which further supported the potential of SBG in the treatment of OSCC.…”
Section: Discussionmentioning
confidence: 72%
“…Src is a non‐receptor protein tyrosine kinase, 9,10 whose overexpression and hyperactivity are associated with tumour mass, metastasis, recurrence, angiogenesis and survival of patients with cancer 14‐16 . Of further note, studies have previously demonstrated that Src is overexpressed in OSCC, including tongue cancer, and there is a significant association of Src overexpression with progression, recurrence and prognosis of OSCC 11,17,18 . These findings strongly suggest Src inhibition as a targeted therapy for solid cancers, including tongue cancer.…”
Section: Introductionmentioning
confidence: 98%